PENGARUH LITERASI KEUANGAN DAN PERENCANAAN KEUANGAN TERHADAP PERTUMBUHAN UMKM DI HARAPAN INDAH - M. Awal Ramadhani Oktavian; M. Daffa Pratama; Indah Dwi Miranti; Lia Maulidia; Meliyanti; Husni Mubarok (CV. ADIBA AISHA AMIRA, 2025)
The growth of Micro, Small and Medium Enterprises (MSMEs) is an important element in the regional economy, including the Harapan Indah area. This study aims to analyze the effect of financial literacy and financial planning on the growth of MSMEs in the region. The research method used is quantitative with a descriptive approach. Data was collected through distributing questionnaires to 100 MSME players selected using purposive sampling technique. Data analysis was conducted using multiple linear regression to test the extent to which the independent variables (financial literacy and financial planning) affect the dependent variable (MSME growth). The results show that both financial literacy and financial planning have a positive and significant influence on MSME growth. This finding confirms the importance of increasing the capacity of MSME actors in understanding financial concepts and designing mature financial strategies to encourage sustainable business growth.